Evaluation of Online Business Tax Application Compliance (Case Study: Mobile Merchant) - Alifa Noura Rachman; Siti Nuryanah (Budapest International Research and Critics University, 2022)
This study aims to evaluate compliance on the implementation of online business taxation, which becomes the responsibility of doing online businesses. A qualitative research method was used in this study thru a case study approach. Data collection was carried out using interview technique with eight interviewees who ran an online business. This study indicates that there is no difference on the tax treatment imposed on online business transactions versus conventional transaction. Income Tax and Value Added Tax are the taxes levied. Online business actors in general are already aware of taxation, such as the purpose of paying taxes, the importance of having a Tax Identification Number (NPWP), the existence of tax penalties if they do not comply with tax regulations, and the tax mechanisms that they must implement when running a business. The majority of online businesses that qualify as MSMEs in the mobile phone industry are already aware and obedient of their tax obligations that they have to pay. Nevertheless, there are still MSME taxpayers who have not complied in applying taxes on online businesses that are run. This is because tax officials' socialization of MSMEs is still ineffective and unevenly distributed. Furthermore, for online businesses established as entity, most of them are obedient in paying and reporting their taxes, but do not fully understand the mechanism for implementing Value Added Tax and Income Tax to run online businesses. As a result, they continue to rely on consultant services to calculate and report taxes.